Month of Birth and Children’s Health in India - Lokshin, Michael; Radyakin, Sergiy (2012)
The authors use data from three waves of the India National Family Health Survey to explore the relationship between the month of birth and the health outcomes of young children in India. They find that children born during the monsoon months have lower anthropometric scores compared with children born during the fall and winter months. The authors propose and test four hypotheses that could explain such a correlation. The results emphasize the importance of seasonal variations in affecting environmental conditions at the time of birth and determining the health outcomes of young children in India. Policy interventions that affect these conditions could effectively impact the health and achievement of these children, in a manner similar to nutrition and micronutrient supplementation programs.